Hubungan Pengetahuan Dan Perilaku Anak Dengan Kebiasaan Jajan Di SDN Banjarbaru Kota 1 (GS) Tahun 2014 - Firyal Yasmin; Maghdalena. A; Muhammad Hadi Saputera; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
School snack food is a problem that needs the public attention, especially parents, educators, and school administrators. School meals and snacks very risky against biological or chemical contamination of the many disturbing health, both short term and long term. Behavior of children to choose snack foods that have bought both positive and negative impacts to the health of the child. There are still many school snacks are not guaranteed health and potentially cause toxicity. This study aims to investigate the correlation of knowledge and behavior of children with the habit of eating snacks in Elementary school 1 (GS) Banjarbaru. This study uses an analytical method with cross sectional design. The number of respondents in this study were mostly less 55. Knowledge is 38,2%, the behavior of most of the approximately 49,1%, majority of ordinary snack, snack habits 67,3%. Based on statistical tests, the results of this study there is correlation with the child's knowledge in the habit of eating snacks SDN Banjarbaru City 1 (GS) and also there is correlation with the child's behavior in the habit of eating snacks SDN Banjarbaru City 1 (GS).